2008
DOI: 10.1080/02640410801956569
|View full text |Cite
|
Sign up to set email alerts
|

Task complexity and sources of task-related information during the observational learning process

Abstract: Although research has examined the influence of various sources of task information for skill acquisition during observational learning, the results have been ambiguous. The purpose of this study was to examine sources of information in relation to the type of task. One hundred and twenty participants were randomly assigned to one of two sets of six treatment strategies: (1) all model demonstrations; (2) model demonstrations with physical practice with knowledge of performance; (3) model demonstrations with ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 41 publications
3
40
0
Order By: Relevance
“…However, Laguna [33] suggests that multiple sources of task-related information are more beneficial for the development of cognitive representations. It was also stated that the simpler the task, the quicker this representation will take place [33].…”
Section: Skill Complexitymentioning
confidence: 99%
See 4 more Smart Citations
“…However, Laguna [33] suggests that multiple sources of task-related information are more beneficial for the development of cognitive representations. It was also stated that the simpler the task, the quicker this representation will take place [33].…”
Section: Skill Complexitymentioning
confidence: 99%
“…Laguna [33] found that performance increased as the number of model demonstrations increased suggesting the need for longer intervention periods or more training sessions with the self-modelling video. Furthermore, the complexity level of the skill needs to be matched to the skill and motor capability level of the performer.…”
Section: Length Of Interventionmentioning
confidence: 99%
See 3 more Smart Citations